PENDEKATAN TOLERANSI DALAM MEWUJUDKAN KERUKUNAN UMAT BERAGAMA (Lex Jurnalica, 2018)
AbstractIndonesia is a country with a pluralistic population, tribal, customary, cultural and religious. Pluralism in religion occurs because of the inclusion of major religions to Indonesia. The development of these religions has made the nation of Indonesia as a religious nation, where religious life can not be separated from the life of the people and the nation of Indonesia. It should not be the basis of the principle of religion to be the basis of the occurrence of splits or endless conflict. In this paper want to discuss about how to realize harmony among religious people in Indonesia. Where according to the author, that the way to realize harmony among religious people in Indonesia is to foster back the spirit of tolerance among religious communities. Keywords: tolerance, harmony, religious people  AbstrakIndonesia adalah termasuk negara yang penduduknya majemuk dalam suku, adat, budaya dan agama. Kemajemukan dalam hal agama terjadi karena masuknya agama-agama besar ke Indonesia. Perkembangan agama-agama tersebut telah menjadikan bangsa Indonesia sebagai bangsa yang beragama, dimana kehidupan keagamaan tidak dapat dipisahkan dari kehidupan masyarakat dan bangsa Indonesia. Seharusnya perbedaan prinsip agama janganlah dijadikan dasar dari terjadinya perpecahan atau pun konflik tak berkesudahan. Dalam tulisan ini ingin dibahas mengenai bagaimana cara mewujudkan kerukunan antar umat beragama di Indonesia. Dimana menurut penulis, bahwa cara mewujudkan kerukunan antar umat beragama di Indonesia adalah dengan memupuk kembali semangat toleransi di kalangan umat beragama. Kata kunci: toleransi, kerukunan, umat beragama